REPRESENTASI KASUS PEMBUNUHAN JESSICA KUMALA WONGSO PADA FILM ICE COLD: MURDER, COFFEE, AND JESSICA WONGSO - Alya Khoirunnisa, Mayfida; Surayya Ulfa, Nurist; Noor Rakhmad, Wiwid (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
The cyanide coffee case in 2016 resulted in the death of Wayan Mirna Salihin, and Jessica Wongso had to serve a 20-year prison sentence. In 2023, the documentary Ice Cold: Murder, Coffee, and Jessica Wongso appeared, which raised the story and became a hot topic of conversation among the public. The purpose of this study was to find out how the Jessica Wongso murder case is represented in the film Ice Cold: Murder, Coffee, and Jessica Wongso. This study uses a qualitative approach with John Fiske's Semiotic analysis method at three levels, namely: reality, representation, and ideology. This analysis includes how the film depicts events, characters, and narratives that can influence the audience's perception of Jessica as the accused. The results of this study show First, how the media shapes public opinion towards Jessica Wongso. Through CCTV footage, interviews, and reconstructions of events that display certain narratives that emphasize the mystery and doubt about Jessica's guilt. Second, cinematic techniques such as camera angles, lighting, and background music to create tension strengthen the narrative that is being conveyed. Third, the narrative in this film suggests that Jessica may be a victim of injustice in the legal system and the media, where the film questions whether justice has truly been served. And finally, the media has a great influence in shaping public opinion, which as depicted in the media in this film emphasizes how a suspect can be perceived based on the social construction formed by the media.